PENGEMBANGAN DESA WISATA MELALUI DIGITALISASI MEDIA PROMOSI DI DESA NONGKOSAWIT, KEC. GUNUNGPATI, KOTA SEMARANG - Sri Wahyuni; Setyoningsih Wibowo; Fitri Yulianti (JURNAL PENGABDIAN MANDIRI, 2023)
Promotion is one of successful keys on business; and so on business of tourism village. Nongkosawit tourism village which is located on sub-district Gunungpati, Semarang city Central Java is one of local tourism village that has several tourism destination to be developed. It has big problem on promoting its beautiful part of tourism destination. Besides, it has these following problems to be solved: 1). Nongkosawit tourism village is not promoting abroad yet, so it is just visited by local and domestic tourists; 2). The villagers do not use social media yet to promote it creatively; and 3). The villagers do not well-know information technology yet to make promotion media through social media world-wide. On conducting this service, the team made 2 sessions: workshop and guidance by the workshop to the audiens from tourism management department (Pokdarwis) and youth department (karang taruna) Nongkosawit village. They got workshop about how to make a video Canva-based and using an or some appropriate hashtag as its caption of the video. Hashtag is something important to be written because it is the “keywords” and also “address” of viewers when they want to look for a specific information, such as tourism village on semarang, etc. trending topic can also be found by clicking the correct hashtag, so hashtag is something that must be mastered by they who are on tourism village business. The aims of this public service are: 1) training the audiens to produce something related to technology-based media that can invite abroad visitors; 2) training the audiens to create a video to be uploaded on their social media; and 3) getting the audiens and information technology closer to promote Nongkosawit tourism village abroad. From this public service activity, the team can also publish its activity on seminar namely SNHP 2023 and 3 electronic news papers.